Application of Mundel Theory in Measuring Operational Productivity at Waroeng Tenda Gaul Restaurant, UGM Valley Branch - Putra, Radjandra; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : To analyze the factors affecting operational productivity at Waroeng Tenda Gaul Restaurant, Lembah UGM branch, using Mundel’s Theory as a framework, and to provide strategic recommendations for optimizing labor utilization, improving service efficiency, and minimizing raw material waste Design/Methode/Approach : This research adopts a descriptive case study approach with a combination of qualitative and quantitative methods to analyze operational productivity at Waroeng Tenda Gaul Restaurant, Lembah UGM branch. The study is designed to explore, describe, and evaluate the factors affecting productivity by using Mundel’s Theory, which focuses on the relationship between inputs (resources) and outputs (results) in operational systems. Research Finding : The analysis of operational productivity at Waroeng Tenda Gaul Restaurant, Lembah UGM branch, reveals several key findings based on data collected through observation, interviews, documentation, and time-motion study. These findings are categorized based on Mundel’s productivity dimensions: effectiveness, efficiency, and utilization. Theoretical contribution/Originality : This study contributes to the existing literature on operational productivity by applying Mundel’s Theory of Productivity in a context that has received limited academic attention: a mid-scale, fast-service restaurant specializing in traditional Indonesian cuisine. While previous studies have broadly discussed operational efficiency in the food and beverage industry, this research offers a more focused and practical application of Mundel’s framework in a real-world SME setting. Practitionel/Policy implication : The findings of this study offer several practical implications for both business practitioners and policymakers, particularly in the context of small and medium-sized enterprises (SMEs) in the culinary sector Research limitation : While this study provides valuable insights into the operational productivity of Waroeng Tenda Gaul Restaurant using Mundel’s Theory, several limitations should be acknowledged